Influence of TiO2/Fe2O3 interfacial layers on optical properties under visible light - Thongsuwan W. (2017)
© 2016 Elsevier B.V. High porous TiO 2 /Fe 2 O 3 multilayer films were successfully prepared on glass substrates via a simple and low cost sparking process. TiO 2 and Fe 2 O 3 nanoparticles with an average size of 20 nm were generated on the substrate. X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and Raman spectroscopy results showed that the annealed films (250 and 450 °C) were composed of anatase TiO 2 and hematite Fe 2 O 3 phase. The results of ultraviolet/visible (UV/vis) spectroscopy showed that the transmittance rapidly decreased at the wavelength lower than 600 nm and then slightly increased at the wavelength over 600 nm. Furthermore, the absorption ability of the TiO 2 /Fe 2 O 3 films increased with an increase in the number of interfacial layers.